Cultural ties of the Croatian and Slovene population in the wider area of Čabar - Josipovič, Damir (Razprave in gradivo - Inštitut za narodnostna vprašanja (1990), 2024)
The paper discusses the impact of recent socio-economic and geopolitical changes on cultural ties and ethnic identity formation in the wider area of Čabar, Croatia. It emphasises the importance of understanding the historical context of cross-border relations in this geographically peripheral border region. To assess the specific position of relative isolation, a robust interdisciplinary methodological approach was used, combining the analysis of historical documents, registry books, and population censuses with qualitative methodology like in-depth semistructured interviews with local residents. To assess the specific local interrelations, the patterns of population migration and cross-border marriages (presented in the appendix) were reconstructed and exa-mined. Changes that occurred after the dissolution of Yugoslavia and the establishment of new independent states shed new light on how the local populace reproduced their identity.
Keywords: cross-border migration; Čabar/Čeber; ethnic identity; etnična identiteta; jezikovni odnosi; linguistic relations; prekomejne migracije; Slovene-Croatian cross-border marriages; slovensko-hrvaške prekomejne poroke; Upper Kolpa/Kupa Valley; Zgornja Kolpa/Kupska dolina